What Role Do Career Growth and Skills Play as Additional Factors in the Connection Between Employee Engagement and Job Performance? - Turki Muhammad; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
At Bank Jatim Ponorogo, the objective of this study is to investigate the ways in which career advancement and increasing one's level of expertise influence employee performance. The level of employee engagement will be a variable that will be utilised to assist with the investigation. Data was collected through the use of Structural Equation Modelling (SEM) in conjunction with the Partial Least Squares (PLS) method that was administered to 74 individuals through the use of questionnaires. A significant and favourable impact on employee engagement is demonstrated by the findings, which indicate that both personal career advancement and expertise play a significant role. In addition, employees' work is immediately improved when they are given opportunities to further their careers. Nevertheless, the findings indicate that the level of expertise and employee involvement does not have a significant impact on the degree to which employees perform their duties effectively. Further, the relationship between career advancement, competency, and success at Bank Jatim Ponorogo is not mediated by employee engagement, which does not serve as a go-between. These findings provide us with further information regarding the ways in which job development and skills influence performance. Despite the fact that they demonstrate the significance of involvement, it is not possible for it to totally cure the problem in this instance.